Can genetic testing help in the management of dyslipidaemias?. Issue 4 (August 2020) - Lazarte, Julieta; Hegele, Robert A.
Abstract : Purpose of review: The aim of this study was to evaluate the potential role of genetic testing, particularly next-generation DNA sequencing, in diagnosing and managing dyslipidaemias, particularly monogenic dyslipidaemias. Recent findings: Targeted DNA sequencing of the genes causing monogenic dyslipidaemias is becoming more accessible. Some societies' position statements advise selective utilization of DNA testing in combination with clinical and biochemical assessment. However, high-quality peer-reviewed evidence showing that a DNA-based diagnosis impacts upon long-term patient outcomes is currently lacking. Nonetheless, we show anecdotal examples of tangible clinical actions following from a genetic diagnosis. In any event, care must be taken when interpreting genetic reports. We strongly feel that expertise in both genetics and dyslipidaemias is required to adequately interpret and report results to patients, as well as to make informed treatment decisions that can have a potential lifelong impact. Summary: There are some examples of monogenic dyslipidaemias for which having a molecular diagnosis might beneficially affect patient outcomes, for example certain cases of suspected familial hypercholesterolemia, familial chylomicronemia syndrome, sitosterolemia or lysosomal acid lipase deficiency. In general, we recommend limiting genetic testing to selected cases of monogenic dyslipidaemias. Finally, we advise that there is currently no proven clinical benefit in testing for polygenic dyslipidaemias.